SILODOSIN AS A MEDICAL EXPULSIVE THERAPY FOR DISTAL URETERAL STONES IN THE PAKISTANI POPULATION - Kashif Bangash; Hassan Mumtaz; Hassan ulHussain; Sami Ullah; Syeda Tayyaba Rehan; Khursheed Anwar; Areesha Afzal; Kamran Majeed; Durishahwar Maqbool; Fayyaz Ali Haider; Faria Mumtaz (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
IntroductionRenal stones are a one of leading problems in today’s world. Along with renal stones, ureteral stones also cause significant disturbance in daily living. This is the first research done on the Pakistani population for determining the efficacy of silodosin as MET for distal ureteral stones. Materials and methodologyThis Prospective Cohort study was conducted at Urology Department, KRL Hospital Islamabad from May 2021 to April 2022. Our study comprised 160 individuals with distal ureteric stones of 10mm or less. Silodoso (Silodosin) was prescribed to all patients who came to the urology outpatient department, and their contact information was recorded. Patients were called for follow-up on a weekly basis for up to 3 weeks to make sure that the stone was passing through their urine. The significance of p-value less than 0.05 and odds ratios were examined using the Chi-square test and risk variables for distal ureteral stones. Quality of life was assessed using the Wisconsin Stone (WISQOL) questionnaire.ResultsA whopping 94% of the stones were expelled taking an average of 7.17 days. There are 6.6 times increased risks of forming a stone that is at least 5 mm in diameter in patients between the ages of 41 and 80. Men were 1.4 times more likely than females to have ureteric stones (odds ratio = 1.486, 95 per cent confidence interval [CI] = 1.302-1.696">OR = 1.486). The average quality of life improved after the treatment was 38.87.ConclusionAccording to the results of this study, silodosin is regarded as safe and effective in the treatment of non-complicated distal ureteral stones ranging from 4 to 7 mm in diameter. The cost-effectiveness of silodosin gives it an edge over other alpha-blockers for medical expulsive therapy.Research Registration: Chinese Clinical Trial Registry (ChiCTR2200060517)